2018
DOI: 10.1098/rsbl.2018.0470
|View full text |Cite
|
Sign up to set email alerts
|

Water-repellent plant surface structure induced by gall-forming insects for waste management

Abstract: Many animals and plants have evolved elaborate water-repellent microstructures on their surface, which often play important roles in their ecological adaptation. Here, we report a unique type of water-repellent structure on a plant surface, which develops as an insect-induced plant morphology in a social context. Some social aphids form galls on their host plant, in which they produce large amounts of hydrophobic wax. Excreted honeydew is coated by the powdery wax to form ‘honeydew balls’, which are actively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…The open galls possess opening(s) on the underside of the gall, so that aphids are able to dispose colony wastes through the openings. Previous studies reported that soldier nymphs in the open galls perform cleaning behavior by pushing or rolling honeydew balls, cast-off skins, and cadavers out of the openings (Aoki, 1980; Aoki and Kurosu, 1989; Benton and Foster, 1992; Uematsu et al, 2018). Inhibition of the waste disposal by turning the gall orientation upside down (the openings to be upward) resulted in high mortality of the aphids inside, indicating that gall cleaning is indispensable for survival of the gall inhabitants (Benton and Foster, 1992).…”
Section: Gall Cleaning and Wax Production By Aphids In Open Gallsmentioning
confidence: 99%
See 4 more Smart Citations
“…The open galls possess opening(s) on the underside of the gall, so that aphids are able to dispose colony wastes through the openings. Previous studies reported that soldier nymphs in the open galls perform cleaning behavior by pushing or rolling honeydew balls, cast-off skins, and cadavers out of the openings (Aoki, 1980; Aoki and Kurosu, 1989; Benton and Foster, 1992; Uematsu et al, 2018). Inhibition of the waste disposal by turning the gall orientation upside down (the openings to be upward) resulted in high mortality of the aphids inside, indicating that gall cleaning is indispensable for survival of the gall inhabitants (Benton and Foster, 1992).…”
Section: Gall Cleaning and Wax Production By Aphids In Open Gallsmentioning
confidence: 99%
“…Inhibition of the waste disposal by turning the gall orientation upside down (the openings to be upward) resulted in high mortality of the aphids inside, indicating that gall cleaning is indispensable for survival of the gall inhabitants (Benton and Foster, 1992). Besides, aphids produce large amounts of powdery wax, which coats the excreted honeydew to form unsticky “marbles” or “honeydew balls” (Pike et al, 2002; Kutsukake et al, 2012; Uematsu et al, 2018). The wax-coated honeydew balls are repelled by the gall inner wall so that the aphids can easily push them without being wet or contaminated.…”
Section: Gall Cleaning and Wax Production By Aphids In Open Gallsmentioning
confidence: 99%
See 3 more Smart Citations